The emergence of Fanconi anaemia type S: a phenotypic spectrum of biallelic BRCA1 mutations - Hughes, Tirion; Rose, Anna M. (Frontiers in Oncology, 2023)
BRCA1 is involved in the Fanconi anaemia (FA) pathway, which coordinates repair of DNA interstrand cross-links. FA is a rare genetic disorder characterised by bone marrow failure, cancer predisposition and congenital abnormalities, caused by biallelic mutations affecting proteins in the FA pathway. Germline monoallelic pathogenic BRCA1 mutations are known to be associated with hereditary breast/ovarian cancer, however biallelic mutations of BRCA1 were long predicted to be incompatible with embryonic viability, hence BRCA1 was not considered to be a canonical FA gene. Despite this, several patients with biallelic pathogenic BRCA1 mutations and FA-like phenotypes have been identified -defining a new FA type (FA-S) and designating BRCA1 as an FA gene. This report presents a scoping review of the cases of biallelic BRCA1 mutations identified to date, discusses the functional effects of the mutations identified, and proposes a phenotypic spectrum of BRCA1 mutations based upon available clinical and genetic data. We report that this FA-S cohort phenotype includes short stature, microcephaly, facial dysmorphisms, hypo/hyperpigmented lesions, intellectual disability, chromosomal sensitivity to crosslinking agents and predisposition to breast/ovarian cancer and/or childhood cancers, with some patients exhibiting sensitivity to chemotherapy. Unlike most other types of FA, FA-S patients lack bone marrow failure.